Training of skills of independent activities of primary school pupil's during lessons of mathematics in Lithuania (6–9th decades of the 20th century) - Ažubalis, Algirdas (Lietuvos matematikos rinkinys, 2004)
10 articles have been publicised in the Lithuanian periodicals in order to discuss the problem above. Some selections of independent mathematical works have been publicised. The exercise books of practical works of mathematics are publicised from the beginning of the 8th decade.
Keywords: independent activities; primary school pupils; lessons of mathematics